Analyze the Polishing Process Unit Dynamics in PT. SIPL Using Artificial Neural Networks - Kusnandi Sugiato; Totok Sohartanto (IPTEK Journal of Proceedings Series, 2020)
The wastewater treatment plant in the industry aims to reduce hazardous high concentrations of industrial products waste to the environment by using biological processes. In biological waste treatment, the role of micro biological conditions is very important to produce effluent results in accordance to government regulations. Utilization of automation technology in wastewater treatment plants to improve the ability of operators to monitor and operate the waste treatment process optimally. With technology of polishing unit artificial neural network (ANN) modeling to obtain the accuracy of wastewater quality index prediction. This study aims to analyze the dynamics of the polishing unit process in PT. SIPL through a simulation of polishing unit process dynamics model by using artificial neural networks. The dynamics analysis results of the polishing unit from artificial neural network is similar with the dynamics of actual polishing unit process. The error between dynamics analysis of polishing unit modeling by artificial neural network and data of polishing unit actual is very small. Therefore modeling with artificial neural networks for polishing unit can be used to describe the actual polishing unit.